Promoting the Decay of Sea-Ice - Mellor, Malcolm (ARCTIC, 1963)
Proposes a method for hastening the spring melting by hosing the ice with sea water. This would raise the salinity of the surface from approx. 5 per mil in the Arctic, to 20 or 30 per mil, resulting in increased absorption of solar radiation, greater surface heat, etc., which in turn would weaken the ice. This method, utilizing submersible pumps, should be relatively inexpensive.